2019
DOI: 10.1007/s10509-019-3690-1
|View full text |Cite
|
Sign up to set email alerts
|

Evolution implications of neutron star magnetic fields: inferred from pulsars and cyclotron lines of HMXBs

Abstract: The evolution of neutron star (NS) magnetic field (Bfield) has long been an important topic, which is still not yet settled down. Here, we analyze the NS B-fields inferred by the cyclotron resonance scattering features (CRSFs) for the high mass X-ray binaries (HMXBs) and by the magnetic dipole model for the spin-down pulsars. We find that the B-fields of both the 32 NS-HMXBs and 28 young pulsars with the supernova remnants follow the log-normal distributions, with the average values of 3.4 × 10 12 G and 4.1 × … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 98 publications
3
8
0
Order By: Relevance
“…Additionally, because the periods for most rotating radio transients (RRATs) and intermittent pulsars are greater than 0.5 s (McLaughlin et al 2006;Kramer et al 2006), we eliminate these special radio pulsars from our samples. Therefore, we regard the radio pulsars with spin periods of less than 0.5 s to be the young pulsar, and they are roughly consistent with the arguments based on that their magnetic fields are comparable with those measured by cyclotron absorption lines of X-rays (Ye et al 2019).…”
Section: Data Selectionsupporting
confidence: 84%
“…Additionally, because the periods for most rotating radio transients (RRATs) and intermittent pulsars are greater than 0.5 s (McLaughlin et al 2006;Kramer et al 2006), we eliminate these special radio pulsars from our samples. Therefore, we regard the radio pulsars with spin periods of less than 0.5 s to be the young pulsar, and they are roughly consistent with the arguments based on that their magnetic fields are comparable with those measured by cyclotron absorption lines of X-rays (Ye et al 2019).…”
Section: Data Selectionsupporting
confidence: 84%
“…Thus, strong magnetic fields measured for NSs in HMXBs (B p ∼ 10 12 G) indicate that there is no significant magnetic field decay on timescales up to ≈ 2 × 10 8 years [146]. This is also in correspondence with results in [144] where the authors also concluded that fields 10 13 G do not decay significantly.…”
Section: High-mass X-ray Binariessupporting
confidence: 84%
“…In both cases there are two independent approaches to measure the NS magnetic field: (1) based on NS spin properties and X-ray luminosity, and (2) based on X-ray absorption lines (see e.g. [144] and references therein). The first approach usually suggests that the NS spin period stays close to the equilibrium period.…”
Section: High-mass X-ray Binariesmentioning
confidence: 99%
“…Thus, strong magnetic fields measured for NSs in HMXBs (B p ∼ 10 12 G) indicate that there is no significant magnetic field decay on timescales of up to ≈2 × 10 8 years [149]. This is also in correspondence with the results in [147], where the authors also concluded that fields 10 13 G do not decay significantly.…”
Section: High-mass X-ray Binariessupporting
confidence: 82%
“…In both cases, there are two independent approaches to measure the NS magnetic field: (1) based on NS spin properties and X-ray luminosity, and (2) based on X-ray absorption lines (see, for example, [147] and the references therein). The first approach usually suggests that the NS spin period stays close to the equilibrium period.…”
Section: High-mass X-ray Binariesmentioning
confidence: 99%